A cláusula penal e sua limitação no ordenamento jurídico brasileiro e no direito estrangeiro - Trubilhano, Fabio Souza (2010)
The present work objective is the study goal about the payment penalty clause and its limitations in Brazilian and foreign law, especially german, French and Italian civil code. As regards the Brazilian law, this study focuses on the general rule in the civil code and in the legislations dealing with specific on limitation of penalty. The objective of this work is to highlight the values that underpin the rules which stipulate limitations to contractual fines both as regards the general rules as the specific business as well as a comparative study between the Brazilian legal system and the foreign law and about the general rules for the limitation and reduction of the penalty clause. The reason of studying this subject is the wide use of conventional penalty daily in business, in the most variety forms of contracts, the advantages and the disadvantages of limiting the fine under contract. The work is present, because not only in Brazil but also in several countries the debate is fecund, and doctors study and discuss the theme. The methods of approach used in this research were the hypothetical-deductive and dialectical; methods of procedure, essentially, the historic, comparative and structuralist; and bibliographic research, involving doctrine, homeland and foreign legislation and jurisprudence. The results confirm the hypothesis that the Brazilian legislation, in determining a general rule to the limit of the fine contractual, avoids, up the of conclusion of the contract, the disparity in fixing the quantum of the penalty clause, and also confirm, that limitations differentiated for the penalty clause, by reason of special legislation, considering the social and economic objectives in each modality of business, and also the fact that the greater the limit, more protected will be the debtor, but less strong will be the main mandatory vinculum